Film and modern American art the dialogue between cinema and painting - Manthorne, Katherine 1952- (Routledge, 2019)
Between the 1890s and the 1930s, movie going became an established feature of everyday life across America. Movies constituted an enormous visual data bank and changed the way artist and public alike interpreted images. This book explores modern painting as a response to, and an appropriation of, the aesthetic possibilities pried open by cinema from its invention until the outbreak of World War II, when both the art world and the film industry changed substantially. Artists were watching movies, filmmakers studied fine arts; the membrane between media was porous, allowing for fluid exchange. Each chapter focuses on a suite of films and paintings, broken down into facets and then reassembled to elucidate the distinctive art-film nexus at successive historic moments
Keywords: Art and motion pictures / United States; Painting, American / 19th century / Themes, motives; Painting, American / 20th century / Themes, motives; Motion pictures / United States / History and criticism